Investigation on flexural behavior of a new-type composite column with steel angles. Issue 5 (2nd September 2020) - Ding, Jie; Zou, Yun; Wang, Cheng-Quan; Zhou, Hang-Fei; Li, Tian-Qi
ABSTRACT: A novel precast composite column with L-shape steels and infilled reinforced concrete (LSRC) is proposed and assessed by experimental research and numerical simulation. The LSRC column is constructed with four L-shape steels placing at corners, a reinforced cage placing outside and the casted concrete. The L-shape steels are connected by batten plates and the reinforcement cage is made up of longitudinal bars, hoops, and two-way ties. In this paper, 3 LSRC slender columns and a conventional concrete-filled steel tube column with encased concrete (CFTEC) are tested and compared to investigate their failure modes, flexural strength, and strains of concrete and steel at mid-span. The results show that the LSRC column has more sufficient plastic deformation ability and steel utilization than the CFTEC column, and exhibits the typical flexural failure mode. Furthermore, the 3D finite element model is also established to analyze the contribution of components, interaction mechanism between steel angle and concrete, and the effect of different factors on flexural behavior of LSRC columns. Based on the test and numerical results, the formula for calculating the bending capacity of LSRC column is proposed, and the predicted results agree well with the experimental and numerical values.